Pengaruh Model Discovery Learning Berbantuan Media PhET Terhadap Hasil Belajar Fisika Peserta Didik Kelas XI SMAN 1 Kediri Tahun Ajaran 2017/2018 - Hamidah Lidiana; Gunawan Gunawan; Muhammad Taufik (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
This research aimed to figure out the effect of discovery learning using PhET to the learning outcome in physics of the second-grade students in SMAN 1 Kediri Academic Year 2017/2018. This research was conducted as the result of experiment using non-equivalent control group design. The population of this research was the whole second-grade students in SMAN 1 Kediri. To limit the sample, surfeited sampling was applied consisting the students in class XI MS I as the experiment class and class MS II as the control class. Research instrument used was the multiple-choice test after the tests of validity, reliability, discrimination power, and difficulty level have been done. The increasing of the learning outcome was defined from the result of N-gain test per sub-chapter. The result of this research showed that the learning outcome of the students has increased to both classes. This proved that discovery learning method using PhET has succeeded in increasing the studentsÃ¢â¬â¢ learning outcome for Physics.